Historical roots of Agile Methods: Where did “Agile Thinking” come fro m? - Abbas, Noura; Gravell, Andrew M.; Wills, Gary B. (Springer Berlin Heidelberg, 2008)
The appearance of Agile methods has been the most noticeable change to software process thinking in the last fifteen years [16], but in fact many of the “Agile ideas” have been around since 70’s or even before. Many studies and reviews have been conducted about Agile methods whic h ascribe their emergence as a reaction against traditional methods. I n this paper, we argue that although Agile methods are new as a whole, they have strong roots in the history of software engineering. In add ition to the iterative and incremental approaches that have been in us e since 1957 [21], people who criticised the traditional methods sugge sted alternative approaches which were actually Agile ideas such as th e response to change, customer involvement, and working software over documentation. The authors of this paper believe that education about the history of Agile thinking will help to develop better understandin g as well as promoting the use of Agile methods. We therefore present and discuss the reasons behind the development and introduction of Agi le methods, as a reaction to traditional methods, as a result of peopl e’s experience, and in particular focusing on reusing ideas from histo ry.
Keywords: Agile methods; Software Development